Pembelajaran Berbasis Masalah Pada Mata Kuliah Keterampilan Berbicara Pada Mahasiswa Disibilitas Tuna Daksa - Pahruddin; Gani, Ramlah H. A.; Wijaya, Herman (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
he application of problem-based learning to participants with disabilities is very appropriate to improve their speaking skills. The purpose of this study was to find out the application of problem-based learning to students with disabilities in the process of learning to speak. The method used is to use the Borg & Gall type of development using 7 stages which are divided into 3 parts, namely preliminary studies, product development and testing and finalization. The results of this study are the introduction (Rationalization of innovation, problem solving models, supporting theories for the development of learning models); Learning model with problem-based learning (study of problem-based learning approaches); and instructions for implementing the problem-based learning model (Planning, Implementation, and Evaluation) accompanied by a video of the implementation of the learning activities. In addition, the learning process also produces hand outs and learning models.